Catecholamine: Air/Water Interfacial Formation of Freestanding, Stimuli‐Responsive, Self‐Healing Catecholamine Janus‐Faced Microfilms (Adv. Mater. 45/2014). (December 2014) - Hong, Seonki; Schaber, Clemens F.; Dening, Kirstin; Appel, Esther; Gorb, Stanislav N.; Lee, Haeshin
<x xml:space="preserve">Abstract</x> S. N. Gorb, H. Lee, and co‐workers show on page 7581 the first report on an adhesive catecholamine film that is spontaneously formed at the air/water interface only by the catalytic role of oxygen in air, and its unexplored interfacial properties are examined. The film exhibits a multi‐functionality of strong adhesion, self‐healing, and stimuli‐responsive actuation with a Janus‐faced morphology. This unique air–water interfacial reaction might explain the chemical origin of exoskeleton formation in insects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>